2014
DOI: 10.1289/ehp.1306566
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Modeling of Ozone Levels in Quebec (Canada): A Comparison of Kriging, Land-Use Regression (LUR), and Combined Bayesian Maximum Entropy–LUR Approaches

Abstract: Background: Ambient air ozone (O3) is a pulmonary irritant that has been associated with respiratory health effects including increased lung inflammation and permeability, airway hyperreactivity, respiratory symptoms, and decreased lung function. Estimation of O3 exposure is a complex task because the pollutant exhibits complex spatiotemporal patterns. To refine the quality of exposure estimation, various spatiotemporal methods have been developed worldwide.Objectives: We sought to compare the accuracy of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 19 publications
5
56
1
Order By: Relevance
“…This study showed a strong association between NO 2 and lung cancer. Jerrett and his colleagues later estimated the O 3 exposure in Quebec, QC, Canada using a variety of models, including a Land-Use mixed-effects Regression (LUR) model, a mixture of a Bayesian Maximum Entropy (BME) model and the land-use mixed model as well as a kriging method model [89]. The experimental results proved the superiority of the mixture model (BME-LUR).…”
Section: Land-use Regression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed a strong association between NO 2 and lung cancer. Jerrett and his colleagues later estimated the O 3 exposure in Quebec, QC, Canada using a variety of models, including a Land-Use mixed-effects Regression (LUR) model, a mixture of a Bayesian Maximum Entropy (BME) model and the land-use mixed model as well as a kriging method model [89]. The experimental results proved the superiority of the mixture model (BME-LUR).…”
Section: Land-use Regression Modelsmentioning
confidence: 99%
“…Although researchers chose different predictor variables according to local environments in their LUR models, most of them used linear regression to model the relationship between the pollutant level and the predictor variables [13,15,16,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. One of the assumptions for linear regression is that the observations should be independent of each other.…”
Section: Land-use Regression Modelsmentioning
confidence: 99%
“…Several recent LUR studies have attempted to capture temporal variation, mainly in three ways: (1) by modifying the intercept of LUR models based on a temporal variation observed at background monitoring sites (Gan et al 2011;Nethery et al 2008;Saraswat et al 2013;Slama et al 2007); (2) by adding dummy variables to reflect different periods (Dons et al 2013;Noth et al 2011);and (3) by building LUR models for different periods with dynamic or static variables (Dons et al 2013;Gulliver et al 2011). Other studies even integrated the above methods (Adam-Poupart et al 2014;Patton et al 2014). The first two approaches are limited to producing the same spatial pattern of pollutants over time, because they are based on a typical LUR model.…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%
“…These pollution maps were generated using the R Graph tool [43] and following a Kriging-based interpolation [44]. In particular, a Gaussian distribution is used to adjust the parameters coming from UAV [2] UAV [3] UAV [4] UAV [5] UAV [6] UAV [7] UAV [8] UAV [9] UAV [10] UAV [11] UAV [12] UAV [13] UAV [14] UAV [15] UAV [16] UAV [17] UAV [18] UAV [19] UAV [20] UAV [21] UAV [22] UAV [23] UAV [24] UAV [25] UAV [26] UAV [27] UAV [28] UAV [29] UAV [30] UAV [31] UAV [32] UAV [33] UAV [34] UAV [35] UAV [36] UAV [37] UAV [38] UAV [39] UAV [40] UAV [41] UAV [42] UAV [43] UAV [44] UAV [45] UAV [46] UAV UAV [9]…”
Section: Validation and Simulationmentioning
confidence: 99%